Pharmacokinetics of thiamphenicol glycinate and its active metabolite by single and multiple intravenous infusions in healthy Chinese volunteers - Yang, Bing; Li, Ning; Lu, Yang; Qiu, Zhixia; Zhao, Di; Song, Pengfei; Chen, Xijing (Xenobiotica, 2014)
Abstract 1. The aim of this study was to investigate the pharmacokinetics of thiamphenicol glycinate (TG) and thiamphenicol (TAP) after intravenous (i.v.) infusion of TG hydrochloride in healthy Chinese by evaluating the pharmacokinetic parameters, to provide clinical guidance in TG application. 2. In this double-blinded, phase I clinical trial, 24 healthy Chinese volunteers were recruited and divided into three groups which received a single dose of 500, 1000 or 1500 mg TG hydrochloride. Subjects in 500 mg group received further administrations at the same dose every 12 h for 5 days. The pharmacokinetic parameters were fitted on the basis of bi-phasic or tri-phasic plasma concentration-time profiles of TG and TAP. 3. Following a single dose of 500, 1000, 1500 mg TG hydrochloride, the AUC0-∞ of TG and TAP was 849.1 ± 100.3, 1305.2 ± 301.8, 2315.9 ± 546.9 and 4509.0 ± 565.9, 7506.5 ± 1112.4, 12 613.3 ± 2779.8 µgmL−1 min, respectively. The total clearance of TG was calculated as 0.58 ± 0.07, 0.41 ± 0.10 and 0.68 ± 0.18 L min−1. The transformed rate constant from TG to TAP was fitted as 0.153, 0.113 and 0.118 min−1, respectively. TAP was mainly excreted as unchanged form with no tendency of accumulation via kidney (71.9 ± 19.4%) with the renal clearance estimated at 0.097 L min−1. 4. The established modeling was applied successfully to evaluate the pharmacokinetics of TG and TAP, providing meaningful guidance in TG clinical application.